Determinants of Exclusive Breastfeeding and Immunization Status with ARI Incidence in Toddlers in Central Buton District - Agus Darmawan; Rina Andriani (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
In Indonesia, infants with acute respiratory infections (ARI) are a common occurrence. Many baby deaths are brought on by ARI. The goal of the study was to ascertain the link between the prevalence of ARI in toddlers in the working area of Wamolo Public Health Center, Central Buton Regency, and exclusive breastfeeding and immunization status. Type research uses quantitative methods with a cross sectional study approach. Population is 223 and sample is 70 and sampling method used is purposive sampling. The research data consisted of primary data obtained from questionnaires and secondary data sourced from reports. The SPSS program is used to process the data. Analysis used is univariate and bivariate using chi square test at a 95% confidence level (α = 0.05). Results showed that relationship between exclusive breastfeeding and incidence ARI in toddlers was ρ=0,000 α =0,05 and relationship between immunization status and incidence ARI in toddlers was ρ=0,000 α =0,05. Conclusion shows that relationship between exclusive breastfeeding and immunization status with incidence of ARI in toddlers in working area of Wamolo Health Center, Central Buton Regency.